Reduced adiposity attenuates FGF21 mediated metabolic improvements in the Siberian hamster - Jo E. Lewis (Nature Portfolio, 2017)
Abstract FGF21 exerts profound metabolic effects in Siberian hamsters exposed to long day (LD) photoperiods that increase appetite and adiposity, however these effects are attenuated in short day (SD) animals that display hypophagia and reduced adiposity. The aim of this study was to investigate whether the beneficial effects of a novel mimetic of FGF21 in the LD state are a consequence of increased adiposity or of the central photoperiodic state. This was achieved by investigating effects of FGF21 in aged hamsters, which is associated with reduced adiposity. In LD hamsters with increased adiposity, FGF21 lowered body weight as a result of both reduced daily food intake and increased caloric expenditure, driven by an increase in whole-body fat oxidation. However, in LD animals with reduced adiposity, the effect of FGF21 on body weight, caloric intake and fat oxidation were significantly attenuated or absent when compared to those with increased adiposity. These attenuated/absent effects were underpinned by the inability of FGF21 to increase the expression of key thermogenic genes in interscapular and visceral WAT. Our study demonstrates the efficacy of a novel FGF21 mimetic in hamsters, but reveals attenuated effects in the animal model where adiposity is reduced naturally independent of photoperiod.